Positioning Techniques in Surgical Applications Thorax and Heart Surgery - Vascular Surgery - Visceral and Transplantation Surgery - Urology - Surgery to the Spinal Cord and Extremities - Arthroscopy - Pediatric Surgery - Navigation/ISO-C 3D - Krettek, Christian; Aschemann, Dirk (Springer Berlin Heidelberg : Imprint: Springer, 2006)
The success of an operation depends not only on careful dures with direct visualisation techniques. Special inst- clarification of the indications, selection of the right time ments are only used for one specific purpose; a surgical for operating and technically neat operating techniques, needle today has its own anatomy. In addition, these but also on correct preoperative preparation and positio- aspects are joined by stricter safety conditions, increased ning of the patient. But this aspect in particular is fre- demands made by patients, with the threat of legal con- quently neglected, particularly by young surgeons, becau- quences if something should go wrong in terms of »nihil se technical details of the operation assume far greater nocere« ... attention, underestimating the contribution made by op- We have therefore made an attempt to illustrate a p- timum positioning to a time-saving operation which runs cedure which has proven successful over many years at the as perfectly as possible. How easy is it for an operation to Medical University Hannover. This does not mean that develop complications out of all proportion because the there are not other appropriate or even better suited surgeon forgot certain »minor matters« during preparati- procedures for specific situations, which would ideally ons! Anyone who has witnessed this themselves will ap- supplement the procedure described here. We felt it was preciate just how important exact preoperative planning important to describe safe, practical positioning tech- and preparation is before an operation takes place. ques to simplify each specific operation.